Carbon dots from polyurethane for pH and 4-nitrophenol sensing and selective detection of silver ion (Ag+) - Dela Cruz, Ma. Ivy S.
Polyurethane (PU) foam is an interesting precursor for carbon dot (CD) synthesis because: (1) PU foam waste generation is alarmingly high, and (2) PU is rich in functional groups which is imperative to producing highly photoluminescent CDs. In this study, carbon dots (CDs) were synthesized form polyurethane foam via one-step pyrolysis method. The CD synthesis parameters namely (H2SO4) concentration, reaction time and reaction temperature were modeled and optimized using Box-Behnken design (BBD) of response surface methodology (RSM). The CDs showed a blue-green emission under UV light with an unexpectedly high quantum yield of 33% with respect to quinine sulfate. The CDs were characterized using UV-visible spectroscopy, fluorescence spectroscopy, X-ray photoelectron spectroscopy, Fourier-transformed infrared spectroscopy, dynamic light scattering, and high-resolution transmission electron spectroscopy. They showed excellent sensitivity to pH variations with RGB hue parameter linearly increasing with pH from pH 6 to pH 12. The CDs also exhibited linear RGB parameter with respect to 4-nitrophenol concentration. In addition, the CDs exhibited distinct selectivity to silver ion (Ag+) with a limit of detection of 2.8 uM. Based on these results, pyrolysis is an effective means for PU waste management as waste volume is reduced by 99% and a new resource (e.g., carbon dots) is recovered during the process.